WhatsApp Usage Differences Amongst Genders: An Exploratory Study - Rungta, Shravan (Indian Journal of Marketing, 2015)
Technology (telephone and the Internet) has influenced the medium and nature of communication significantly over the last few years. WhatsApp - the dominant mobile instant messaging service provider has become a revolution overnight, offering nothing much, but a ’communication tool’ to send and receive text, audio, and visual (pictures) messages between individuals and groups. With over 500 million subscribers around the world, this phenomenon has become a subject of intense study for researchers and academicians from across the world in the area of communication and marketing. The present research paper aimed to study the differences in usage of this communication service (WhatsApp) amongst male and female individuals. Literature that deals with socio-linguistic theories has highlighted differences in the way men and women communicate face-to-face and through other mediums. This study indicated that gender did influence the usage of Whatsapp in some cases, but there were a lot of elements like usage style / pattern / preference that showed little or no difference amongst genders. Gender differences were visible in the area of usage of emoticons (greater number of female respondents agreed to use it often); being part of a larger number of groups (men were part of more groups) ; active time spent during the day (men spent lesser time as compared to women) ; changing profile picture and status often (women had the tendency to change the same more number of times) ; sharing emotional outbursts on Whatsapp (women tended to agree to the same more than men) ; and sending pictures of their shopping (merchandise) to friends and family (more women agreed to do that as compared to the male respondents). The research study also found that in a lot of areas, gender did not make a difference, which corroborated with the results of many of the existing studies in this area.